HEART RATE VARIABILITY: CLASSIFICATION AND DYNAMIC SYSTEM ANALYSIS - Martynenko, A.V.; Yabluchansky, M.I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The proposed classification of dynamic HRV processes is based on M-indexes: |М|<0.03 – linear, stationary; 0.3>|М|>0.03 – weakly nonlinear, quasi stationary; 3>|М|>0.3 – nonlinear, transient; |М|>3 – strongly nonlinear, transient. The character of M-index gives following interpretation for direction of dynamic HRV process (integrated for analyzing record): «+»– accelerating; «–»– decelerating. Thus M-indexes introduce generalized basis for allocation of HRV stationary processes: М0 indexes – determine as stationary the whole class on inertial movements in HRV, i.e. movement with constant speed or stochastic vibrations around unchanged frequency; М1 indexes – determine as stationary the whole class of periodical and quasi periodical movements in HRV, the movements which keep constant phase flow what can be achieved by introducing of time arrow; М indexes – consider the whole system of appointed above stationary processes in HRV.